Diffuse Alveolar Hemorrhage and Pulmonary Vasculitides: Histopathologic Findings - Scapa, Jason V.; Fishbein, Gregory A.; Wallace, W. Dean; Fishbein, Michael C. (Seminars in Respiratory and Critical Care Medicine, 2018)
Vasculitides are a heterogeneous group of disorders in which inflammation of blood vessel walls is present at least some time during the course of the disease. Vasculitides can affect any caliber or type of vessel in many anatomic sites; however, the disease can alter more than just vasculature. Given the diversity of vasculitides, in 2012, a revised classification system was proposed to categorize vasculitides by the type of vessel involved including size, function, and structural attributes. In the lung, vasculitis impacts both the pulmonary vessels and parenchyma. Extrapulmonary involvement, particularly with concomitant kidney involvement, is a frequent occurrence. Pulmonary vasculitides often present with hemoptysis, pathologically manifested as diffuse alveolar hemorrhage (DAH) with or without capillaritis and can be life threatening when diffuse throughout the lungs. Etiologies for DAH include both primary and secondary vasculitides, along with collagen-vascular diseases, infection, and drug toxicity. Therefore, diagnosing the specific vasculitic etiology often relies on comprehensive assessment of all clinical, laboratory/serological, imaging, and histopathologic features that may be present. The most common primary pulmonary vasculitides often affect small vessels and are associated with circulating antineutrophilic cytoplasmic antibodies (ANCAs). In the 2012 classification, these include granulomatosis with polyangiitis (formerly Wegener granulomatosis), eosinophilic granulomatosis with polyangiitis (formerly Churg–Strauss' syndrome), and microscopic polyangiitis. Other less frequent vasculitides that are non-ANCA associated or affect medium- to large-sized vessels can have pulmonary involvement. These entities are usually associated with extrapulmonary disease and include polyarteritis nodosa, Takayasu's arteritis, Behçet's disease, and antibasement membrane antibody disease (formerly Goodpasture's syndrome). Although all vasculitides have vessel wall inflammation at some phase in the disease process, their histopathologic findings are as diverse as the group of diseases themselves. The characteristic histologic findings of the pulmonary vasculitides will be reviewed here.
Keywords: vasculitis; ANCA-associated vasculitides; granulomatosis with polyangiitis; microscopic polyangiitis; eosinophilic granulomatosis with polyangiitis; diffuse alveolar hemorrhage